Recurrent DICER1 hotspot mutations in endometrial tumours and their impact on microRNA biogenesis. Issue 2 (6th July 2015) - Chen, Jiamin; Wang, Yemin; McMonechy, Melissa K; Anglesio, Michael S; Yang, Winnie; Senz, Janine; Maines‐Bandiera, Sarah; Rosner, Jamie; Trigo‐Gonzalez, Genny; Grace Cheng, SW; Kim, Jaeyeon; Matzuk, Martin M; et al.
Abstract DICER1 plays a critical role in microRNA (miRNA) biogenesis. Recurrent somatic 'hotspot' mutations at the four metal‐binding sites within the RNase IIIb domain of DICER1 were identified in ovarian sex cord‐stromal tumours and have since been described in other paediatric tumours. In this study, we screened the RNase IIIb domain of DICER1 in 290 endometrial tumours and identified six cases with hotspot mutations, including two cases affected by an atypical G1809R mutation directly adjacent to a metal‐binding site. Using Illumina and Sanger targeted resequencing, we observed and validated biallelic DICER1 mutations in several cases with hotspot mutations. Through in vitro DICER1 cleavage assays, small RNA deep sequencing and real‐time PCR, we demonstrated that mutations adding a positively charged side chain to residue 1809 have similar detrimental effects on 5p miRNA production to mutations at the metal‐binding sites. As expected, 5p miRNAs were globally reduced in tumours and cell lines with hotspot mutations. Pathway analysis of gene expression profiles indicated that genes de‐repressed due to loss of 5p miRNAs are strongly associated with pathways regulating the cell cycle. Using a Dicer1‐null mouse cell line model, we found that expression of DICER1 hotspot mutants promoted cell proliferation, whereas wild‐type (WT) DICER1 inhibited cell proliferation. Furthermore, targets of let‐7 family miRNAs are enriched among the up‐regulated genes, suggesting that loss of let‐7 may be impacting downstream pathways. Our results reveal that DICER1 hotspot mutations are implicated in common malignancies and may constitute a unique oncogenic pathway. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.